Predictive context transfer protocol for mobility management in centralized wireless local area network - Mazlan, Mohammad Hasbullah (2013)
In secured large scale Wireless Local Area Network, Context Transfer (CT) technique has been proposed to reduce the main handover latency component in a secured environment, which is 802.1x authentication phase. In order to achieve seamless handover, this work will use the CT technique to transfer the Pairwise Master Key (PMK) of clients to the new Access Point (AP) before handover process. However the drawback of using CT method is that the AP will receive the context cache even if a mobile user is not roaming, resulting in high memory usage in the AP. In this thesis, a context aware handover management technique is introduced to predict the handover initiation for mobile user in an indoor environment. The predictive technique includes a method called Received Signal Strength (RSS) transition pattern and client’s Moving Weight (MW) to detect handover initialisation for mobile users. This technique will distribute the context cache only when it detects that mobile user is leaving the current AP. Early RSS transition pattern is an enhanced technique that collects RSS data before client reaches the handover threshold and makes the handover decision. Client’s MW technique is able to predict the movement status of mobile user whether it is static or moving within the network coverage. This proposed method is called Predictive Context Transfer (PCT) technique that will be implemented in the Access Controller. PCT is able to reduce the re-authentication latency during the handover process up to 80% and below than 150ms which is the requirement of VoIP standard. Moreover, PCT for handover initialisation using the client’s MW is able to prevent unnecessary handover process and predict when the client is leaving the current network during the handover process.